2005
DOI: 10.1093/jn/135.8.1926
|View full text |Cite
|
Sign up to set email alerts
|

Homeless Youth in Toronto Are Nutritionally Vulnerable

Abstract: This study was undertaken to characterize nutritional vulnerability among a sample of homeless youth in downtown Toronto. Interviews were conducted with 261 homeless youth (149 male, 112 female), recruited from drop-in centers and outdoor locations. Information about current living circumstances, nutrition and health-related behaviors, and 24-h dietary intake recalls were collected, and height, weight, triceps skinfold thickness, and mid-upper arm circumference were measured. A second 24-h dietary intake recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 32 publications
2
58
1
Order By: Relevance
“…-There were no milk product servings in any of the meals. -The estimated average requirements (EAR) are presented for smokers because a high proportion of homeless individuals smoke (20) . The EAR for nonsmokers would be 35 mg/d less.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-There were no milk product servings in any of the meals. -The estimated average requirements (EAR) are presented for smokers because a high proportion of homeless individuals smoke (20) . The EAR for nonsmokers would be 35 mg/d less.…”
Section: Resultsmentioning
confidence: 99%
“…Many programmes rely on donated foodstuffs from food banks (21) and other charitable food redistribution networks, though both the quantity and nutritional quality of foods garnered through this route are limited (22)(23)(24)(25)(26)(27)(28) . Concerns about the appropriateness and effectiveness of these efforts stem from the high levels of food deprivation documented among samples of homeless individuals (15,(17)(18)(19)(20) , and also a recent study in Toronto that found homeless youth who used charitable meal programmes to be as nutritionally vulnerable as those who did not (11,20) . Concerns about the adequacy of nutrition supports for homeless groups are not unique to Canada.…”
mentioning
confidence: 99%
“…While the majority of youth in our study consumed carbohydrates in the acceptable AMDR, their food choices reflect a high intake of simple carbohydrates, mostly void of fiber. Other research with poor youth has also reported problems with constipation (Richards and Smith, 2007;Tarasuk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, homeless youth living without parents, either on the street or in shelters for youth, reported struggling daily to obtain shelter, food, income, and perceived food as a precious commodity (Dachner and Tarasuk, 2002). Strategies used by homeless Canadian youth to acquire food included asking for food from strangers or friends, stealing food, getting food from dumpsters, and eating at charitable meal programs (Tarasuk et al, 2005). Furthermore, homelessness appears to be increasing, and nationwide it is estimated that on any given day approximately 600,000 individuals are homeless, including 200,000 children living in homeless families (Granruth and Smith, 2001).…”
mentioning
confidence: 99%
“…While living on the street or subject to commercial sexual exploitation, children and youth are exposed to physical, mental, and social vulnerability 15,16,17,18 due to their backgrounds, circumstances, and contexts in which their daily life unfolds. Under such conditions they often abuse and develop addiction to drugs and alcohol due to the abundant supply in the street scene 19,20 .…”
Section: Introductionmentioning
confidence: 99%